2021
DOI: 10.3390/recycling6020024
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects on Residents’ Willingness in Waste Sorting to Improve Waste Handling in Dammam City, Saudi Arabia

Abstract: While the total amount of municipal solid waste (MSW) in Dammam city was about 13 million tons in 2013, it is expected to reach about 18.4 million tons in 2025. Although the main problem in Dammam city is an increase in solid waste production without any formal treatment except landfilling, the lack of waste segregation greatly affects the residents’ handling practices of solid waste due to incorrect disposing practices. The objective of this study explored the possibility of Dammam residents’ participation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Waste segregation and recycling at the source is a valuable tool in reducing the volume of waste and the amount of waste disposed of at landfill sites. It is also evident that waste segregation at the source is advantageous, e.g., in terms of the ease in handling, processing, enhancing resource recovery, fostering reuse and recycling, and reducing operational costs [25][26][27]. On the other hand, improper household waste solid management is associated with various health risks [21][22][23][24]27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste segregation and recycling at the source is a valuable tool in reducing the volume of waste and the amount of waste disposed of at landfill sites. It is also evident that waste segregation at the source is advantageous, e.g., in terms of the ease in handling, processing, enhancing resource recovery, fostering reuse and recycling, and reducing operational costs [25][26][27]. On the other hand, improper household waste solid management is associated with various health risks [21][22][23][24]27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The moderating effect of income and market incentives was likewise observed between attitude and willingness to sort and recycle waste in the low-income-level and high-incomelevel groups. In addition, the gender status of the participants had a moderating effect on the relationship between market incentives and willingness to sort and recycle waste in both males and females [26].…”
Section: Introductionmentioning
confidence: 97%
“…In fact, there are several obstacles to sustainability, including public understanding and population expansion. Community members would be more motivated and open to participating if they were made aware of the advantages of source reduction and trash separation (Phan et al, 2021;Altikolatsi et al, 2021;Labib et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…Implementing the 3R strategy (reduce, recycle and reuse) to influence public behavior has recorded some success in a residential estate in the Eastern Province of Saudi Arabia that led to 46.7% garbage reduction from 5625 tons to 3000 tons annually [62]. Another study conducted in Dammam city, Saudi Arabia, revealed that 57.1% and 55.1% of 450 study respondents reported having a positive attitude regarding trash sorting and recycling, respectively [63]. A study in the United Kingdom also showed a positive public response towards trash segregation and its conversion into energy through incineration [64].…”
Section: Attitude Towards Sorting and Recycling Of Trashmentioning
confidence: 99%